Analisis Redaman Sistem Vibrasi Paksa Satu Derajat Kebebasan Pada Simple Vibration Apparatus - Setiawan, Dibyo; Zainuddin, Zainiddin; Thoyib, Ibnu Annas; Kholil, Ahmad; Kusumohadi, Catur Setyawan (Universitas Muria Kudus, 2024)
Vibration testing in the field of mechanical engineering has an important role in planning and maintaining machines to determine whether the design is safe and suitable for application. Newton's second law is a reference for back-and-forth movement around equilibrium both within the system and from outside the system which affects the machine itself, if the frequency of stimulation is equal to one of the system's natural frequencies, then resonance occurs, and dangerously large oscillations, resonance can cause damage to the system. The solution to avoid excessive resonance requires a damper. Forced vibration oscillations are applied by excitation using an unbalanced mass installed on a DC motor unit, the response is a mass deviation to obtain oscillations or time relationships with amplitude, the natural frequency of the system, mass-spring deviation, and characteristics of vibration. This activity aims to analyze the effect of the vibration amplitude of a forced vibration simulator under conditions without damping and using damping. The experimental test method was applied to a forced vibration system with one degree of freedom with an oil and air damper in a simple vibration apparatus simulator, 2 types of unbalanced masses, regulated by rotation up to 500rpm, tested under conditions without a damper, using an oil and air damper. The results of the activity showed that the air-dampening media can limit greater amplitude compared to the oil-dampening media.